1990
DOI: 10.5344/ajev.1990.41.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Translocation of Nitrogen Absorbed During Late Spring by Two-Year-Old Grapevines Grown in Sand Culture

Abstract: Distribution and translocation of spring-applied nitrogen (N) were quantified for two-year-old Chenin blanc grapevines grown in sand culture. Vines were labeled with 15N over a four-week period stretching from the end of bloom to the end of rapid shoot growth. From this stage onwards, vines were fed unlabeled KNO 3, and entire vines were sampled eight times over a period of 11 months. Five samples were taken in the second and three during the third growing season. At the first sampling date (one week after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 23 publications
5
36
0
Order By: Relevance
“…Another study reported that N application during budbreak and the post-harvesting period resulted in the highest content of labeled N in the dormant storage tissue and in the leaf tissue during rapid spring growth and at flowering [18]. A previous 15 N tracer test showed that 15 N urea could be transported to the fine roots at 12-24 h after absorption [19]. In the aforementioned study, both total N and fertilizer N were stored in the roots, especially in the coarse roots, and the growth and development of new organs after germination preferentially utilized the fertilizer N absorbed by the leaves.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Another study reported that N application during budbreak and the post-harvesting period resulted in the highest content of labeled N in the dormant storage tissue and in the leaf tissue during rapid spring growth and at flowering [18]. A previous 15 N tracer test showed that 15 N urea could be transported to the fine roots at 12-24 h after absorption [19]. In the aforementioned study, both total N and fertilizer N were stored in the roots, especially in the coarse roots, and the growth and development of new organs after germination preferentially utilized the fertilizer N absorbed by the leaves.…”
Section: Introductionmentioning
confidence: 95%
“…Fertilizer absorption and utilization have been shown to be dependent upon irrigation techniques [8,9], soil types [10], phenological stages [11], fertilizer amounts and fertilization application frequency [12,13], and fertilizer application methods [14] in grapevines. In terms of fertilizer absorption and utilization in grapevines, it has been reported that nearly 40% of the spring-applied N that is still present in the leaves at harvesting is translocated to the shoots and permanent structures during leaf senescence [15]. The N recovery efficiency (RE N ) of grapevines has been reported to be similar at budbreak (7.1%) and blooming (10.6%) [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations